KONVIVIAL DALAM FILM TAKEN KARYA PIERE MORREL & OLIVIER MEGATON: SUATU ANALISIS PRAGMATIK - LASUT, FRANSISKUS ANGELO; KODONG, FENTJE; SENDUK, ARTER JODI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research entitled â€œConvivial dalam Film Taken by Piere Morel & Olivier Megatonâ€. The success of communication depends on how well a hearer can read the message from the speaker. The purpose of this research is to have a concrete view of how convivial is used in the film Taken. In collecting data, the writer concentrated on the utterances which contain the convivial sentence produced by the characters in the film. The collected data are analyzed based on Leechâ€™s theory. The result shows that there are six types of acts of convivial in the film Taken, they are: offering, promising, thanking, inviting, thanking and congratulating. It is expected that this research will help the students and the other readers in learning the pragmatics aspects, especially about illocutionary act.Keyword: Convivial, Movie Illocutionary act, Pragmatics, Film Taken.